Changes in muscle performance among older adults with myeloid malignancies engaging in a mobile health (mHealth) exercise intervention: a single arm pilot study - Marielle Jensen-Battaglia; Po-Ju Lin; Chandrika Sanapala; Erin E. Watson; Jason H. Mendler; Jane Liesveld; Ying Wang; Elisabeth Hayward; Marissa LoCastro; Soroush Mortaz; Richard F. Dunne; Karen Mustian; et al. (BMC Geriatrics)
Abstract Background Older adults with cancer are vulnerable to declines in muscle performance (e.g., strength, speed, duration of muscular contraction), which are associated with worse cancer-related outcomes. Exercise-based interventions can mitigate these declines, but evidence of their effect among older adults with myeloid malignancies receiving outpatient treatment is limited. We explore change in muscle performance among patients in a single arm pilot study of a mobile health (mHealth) exercise intervention. Methods Patients ≥ 60 years old with myeloid malignancies receiving outpatient chemotherapy completed a home-based resistance band and walking exercise program [EXercise for Cancer Patients (EXCAP)©®] delivered via a mobile application with symptom monitoring [(Geriatric Oncology-EXCAP (GO-EXCAP)] lasting 2 cycles of chemotherapy (approximately 8–12 weeks). Clinical exercise physiologists provided instruction and ongoing support. Upper and lower extremity peak torque (maximum force, newton-meters, Nm), total work (force over entire movement, Nm), and average power (speed of force, watts, W) were assessed using the BIODEX System 4 isokinetic dynamometer. Muscle activation (motor recruitment, millivolts, mV) was captured using the BTS FREEEMG 1000. We report descriptive statistics and within-patient differences from baseline to post-intervention using Wilcoxon signed rank tests (α = 0.10) and effect size (ES, Cohen’s d, 0.20 ≤ small < 0.50, large ≥ 0.80), and explore differences by exercise level (resistance exercise, daily steps). Results A total of 25 patients completed baseline assessments, 23 with muscle performance data at baseline, 16 at post-intervention. Of these, most were male (n = 10, 62.5%) and had acute myeloid leukemia (n = 9, 56.3%). From baseline to post-intervention there were improvements in left shoulder peak torque [mean change = 2.45 (Standard Deviation = 2.41), p = 0.004] and average power [2.29 (3.05), p = 0.033]. Muscle activation increased for left rectus femoris [0.04 (0.04), p = 0.074], right and left biceps brachii [0.03 (0.04), p = 0.012; 0.03 (0.05), p = 0.098, respectively], and left pectoralis major [0.02 (0.03), p = 0.064]. Several measures of peak torque/total work and all measures of muscle activation showed ES ≥ 0.20 for improvement. There were no statistically significant decreases from baseline to post-intervention. Conclusions Older adults with myeloid malignancies participating in a mHealth exercise intervention had stable to improved muscle performance. Further research is needed to establish the preliminary efficacy of this intervention for improving physical performance in this population at high risk for decline. Trial registration clinicaltrials.gov NCT04035499 (registered July 29th, 2019).